Carbon quantum dot material as well as preparation method and application thereof
The carbon quantum dot material and electrospinning technology synthesized by hydrothermal method form modified zinc foil, which solves the problem of zinc dendrites and hydrogen evolution reaction in zinc ion batteries, achieves more stable zinc ion deposition and improves battery performance, and simplifies Large-scale application.
Patent Information
- Application Number
- CN202411459805.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-18
AI Technical Summary
The zinc negative electrode in aqueous zinc ion batteries is prone to form zinc dendrites and hydrogen evolution reactions, resulting in unstable battery performance and short life. Existing modification strategies such as alloying and interface modification have problems such as high cost and reduced energy density.
The hydrothermal method is used to synthesize carbon quantum dot materials rich in zinc-philic functional groups, and combine them with polyacrylonitrile spinning material through electrospinning technology to form a modified zinc foil to form a strong protective layer to inhibit zinc dendrites. React with hydrogen evolution.
Modified zinc foil effectively suppresses volume expansion during charging and discharging, improves cycling stability and ionic conductivity, extends battery life, and reduces the formation of by-products, simplifies large-scale application process.
Smart Images

Figure CN119306209A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery materials, and particularly to a carbon quantum dot material, a preparation method thereof, and an application thereof. Background Art
[0002] Regarding the reserves in nature, the studied aqueous ion batteries include alkali metal cations (Li + , Na + and K + ) and polyvalent ion (Ca 2+ , Mg 2+ , Al 3+ and Zn 2+ ) batteries. Aqueous sodium ion batteries and potassium ion batteries have large raw material storage and low production costs, and have chemical properties similar to those of lithium. However, they face problems such as low energy density and high toxicity. Although polyvalent ions can be used for redox reactions involving multiple electrons to obtain high specific capacity and high energy density, there are still some problems. For example, the deposition and dissolution reversibility of the negative electrode of aqueous calcium ion batteries is poor, and the electrolyte will cause corrosion of the negative electrode and the current collector, resulting in unstable battery performance. In aqueous magnesium ion batteries, Mg 2+ diffuses slowly in the host lattice, there are fewer available positive electrode materials, and the magnesium negative electrode is prone to passivation, further hindering the diffusion of Mg 2+ . Although aqueous aluminum ion batteries have a high volume capacity (8040 mAh cm -3 ), the aluminum negative electrode is prone to form an A12O3 passivation film on the surface in an aqueous electrolyte (4 < pH < 8) and is prone to cause uneven corrosion on the surface of the aluminum electrode, resulting in attenuation of battery efficiency and electrode potential, making the aqueous aluminum ion battery still in the experimental stage and limited to the field of primary battery energy storage. In comparison, aqueous zinc ion batteries use a mild neutral electrolyte, have a high theoretical capacity, a relatively low redox potential, low production costs, and high safety, and stand out among multi-ion aqueous batteries, and are expected to be applied in the fields of grid energy storage and electric vehicles in the future.
[0003] At present, commercial zinc foil is usually used as the negative electrode material of aqueous zinc ion batteries. Although the zinc negative electrode has a high capacity, it is easy to form zinc dendrites and hydrogen evolution reaction during the charge and discharge process, resulting in battery short circuit and internal expansion of the battery, causing irreversible loss of the zinc negative electrode and affecting the battery life. The formation of zinc dendrites is mainly due to the electric field and the uneven distribution of Zn2+ on the negative electrode surface, while the hydrogen evolution reaction is caused by the slow corrosion of the zinc metal negative electrode in the aqueous electrolyte and the decomposition of the electrolyte during the battery cycle charge and discharge. The repeated deposition / stripping process of metallic zinc will lead to the evolution of the electrode and electrolyte interface (i.e., the change of the interface shape). The deposition / stripping process is usually uneven, resulting in irregular surface morphology and the growth of zinc dendrites, which is called the "tip effect". In actual zinc ion battery devices, the dendritic deposition of the zinc negative electrode and the related side reactions (hydrogen evolution reaction, corrosion and passivation) caused by free water restrict its further development, greatly limiting the cycle life of aqueous zinc ion batteries. According to the problems encountered by the zinc negative electrode, those skilled in the art have proposed some design strategies, including main material design, alloying design and interface modification. The main material design usually adopts a porous 3D negative electrode, which can effectively inhibit passivation due to its large specific surface area. In addition, the 3D negative electrode reduces the local current density and promotes the uniform distribution of ions, thereby achieving uniform deposition of Zn. In addition, the gaps in the framework provide sufficient space for zinc deposition, which prevents the short circuit problem caused by dendrite growth to a certain extent. However, there are some problems with the main material design methods, such as electrode deformation problems at high utilization rates, corrosion problems, and reduced energy density due to increased volume caused by alloying. Alloying zinc with other elements can change the physical and chemical properties of the interface, enhance its corrosion resistance, reduce the passivation effect, and reduce the formation of dead zinc. This method is expected to improve the actual utilization rate and overall performance of zinc in secondary batteries. Through the synergistic effect between different elements, the corrosion resistance and hydrogen evolution overpotential of the alloy zinc negative electrode can be significantly improved. However, the alloy zinc negative electrode loses the advantage of high theoretical specific capacity to a certain extent, and the alloy negative electrode often fails quickly due to interface reconstruction during battery charging. Secondly, the use of bulk alloy zinc negative electrode will greatly increase the cost and reduce the energy density. The interface modification strategy mainly includes two methods: electrolyte additives and construction of artificial protective layers. The negative electrode is in direct contact with the electrolyte, and the interface between the two is where zinc deposition and dissolution occur. In addition to the inherent self-modification of the zinc negative electrode, the electrolyte also plays an important role in affecting the performance of the negative electrode. The properties and composition of the electrolyte have a significant impact on the electrochemical behavior, stability and overall performance of the negative electrode. Therefore, changing the composition of the electrolyte or the negative electrode with certain additives can enhance the stability and reversibility of the system. Although preliminary results have been achieved in using additives to solve various problems related to the zinc negative electrode in the system, the development of multifunctional additives is still relatively difficult. Most additives are single-functional, such as only focusing on dendrite growth problems or interface side reactions.In addition, the existing artificial protective layers on the surface of zinc negative electrodes mostly rely on expensive equipment, such as magnetron sputtering, atomic layer deposition (ALD), etc., which is not conducive to the large-scale application of modified zinc negative electrodes. Summary of the invention
[0004] The main purpose of the present application is to provide a carbon quantum dot material and a preparation method and application thereof, which can simultaneously avoid the formation of zinc dendrites and the occurrence of interfacial side reactions.
[0005] To achieve the above-mentioned purpose, the present application provides a method for preparing a carbon quantum dot material, comprising: placing terephthalaldehyde and trifluoromethylbenzonitrile acetonitrile in a sodium methoxide solution for hydrothermal reaction to obtain a carbon quantum dot material.
[0006] Optionally, the mass ratio of terephthalaldehyde to trifluoromethylbenzonitrile is 1:1-2.
[0007] Optionally, the temperature of the hydrothermal reaction is 120-180° C., and the time is 1-5 h.
[0008] Optionally, the sodium methoxide concentration is 0.5-1.5 mol L -1 .
[0009] To achieve the above objectives, the present application also provides a carbon quantum dot material, which is obtained by the above-mentioned method for preparing the carbon quantum dot material, and the carbon quantum dot material has zinc-philic nucleation sites.
[0010] To achieve the above-mentioned purpose, the present application also provides a method for preparing a modified zinc foil, comprising: mixing PAN powder with DMF to obtain a PAN spinning solution; dispersing a carbon quantum dot material in the PAN spinning solution to obtain a mixed spinning liquid; and spinning the mixed spinning liquid onto the surface of the zinc foil by electrospinning to obtain a modified zinc foil.
[0011] Optionally, the mass ratio of PAN powder to DMF is 0.5-1:9, and the mass ratio of carbon quantum dot material to PAN powder is 0.5-1:10.
[0012] Optionally, the electrospinning process specifically includes: pouring the mixed spinning liquid into a syringe, wrapping the zinc foil on the surface of the receiving device, and performing directional spinning at 45-60 degrees to the receiving device; the electrospinning speed is 0.5-2 mL h -1 , the drying time is 4-8 h.
[0013] To achieve the above objectives, the present application also provides a modified zinc foil, which is obtained by the above-mentioned preparation method of the modified zinc foil.
[0014] To achieve the above objectives, the present application also provides an application of a modified zinc foil in a negative electrode material of a zinc ion battery.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The preparation method of the carbon quantum dot material of the present invention, the carbon quantum dot material rich in various types of zinc-philic functional groups synthesized by the hydrothermal method strategy, can improve the electric field distribution on the zinc metal surface, and then uniform zinc ion deposition and nucleation process, and avoid zinc dendrite formation. The preparation method of the modified zinc foil of the present invention, the high adhesion of the spinning material and the interaction between a large amount of fluorine elements and zinc metal in the carbon quantum dots provide a strong guarantee for the adhesion of the protective layer and the zinc metal, and then form a protective layer with excellent mechanical properties, which can effectively inhibit volume expansion during high current or high capacity cycles; it has good cyclability during the charge and discharge process, and due to the strong adhesion, there will be no failure phenomena such as the protective layer falling off; the internally doped carbon quantum dot material contains a large number of polar functional groups, so the ionic conductivity of the material is improved to a certain extent; the modified zinc foil of the present invention, as the negative electrode material of the aqueous zinc ion battery, has a carbon quantum dot material rich in negatively charged functional groups that can repel sulfate ions in the electrolyte, thereby inhibiting the formation of by-products; the simple operation of the electrostatic spinning process is expected to accelerate the large-scale application of the modified negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a TEM image of a carbon quantum dot material for this application; Figure 2 for Figure 1 FT-IR image of carbon quantum dot material; Figure 3 A schematic diagram of the synthesis of a modified zinc foil for this application; Figure 4 This is the SEM image of Zn@PCDs prepared in Example 1; Figure 5 This is the structural diagram of Zn@PCDs prepared in Example 1; Figure 6 Schematic diagram of the mechanism of Zn@PCDs prepared in Example 1 being used as the negative electrode of zinc ion battery; Figure 7 This is a rate performance diagram of the PCDs composite material prepared in Example 1 under different current density conditions; Figure 8 This is a long cycle performance diagram of the PCDs composite material prepared in Example 1 under different current density conditions.
[0017] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical solutions and advantages of this application clearer, the technical solutions in this application will be clearly and completely described below in conjunction with the drawings in this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0019] The first embodiment of the present invention provides a method for preparing a carbon quantum dot material, which specifically comprises the following steps: Step S1, placing terephthalaldehyde and trifluoromethylbenzonitrile acetonitrile in a sodium methoxide solution for hydrothermal reaction to obtain a carbon quantum dot material. The specific steps may be: According to the mass ratio of 1:1-2, first dissolve trifluoromethylbenzonitrile in 50 mL of 0.5-1.5 mol L -1 The mixture is added to a sodium methoxide solution and stirred for 10-20 min until the substances are uniformly dispersed to obtain a mixed solution; terephthalaldehyde is then added to the mixed solution and ultrasonically treated for 10-20 min to obtain a mixed reaction liquid; the mixed reaction liquid is subsequently transferred to an autoclave, subjected to a hydrothermal reaction at 120-180° C. for 1-5 h, and naturally cooled to room temperature, and the reaction product is purified to obtain FN-CDs material, i.e., carbon quantum dot material.
[0020] The purification process can be as follows: dilute the mixture with 100 mL of deionized water, then centrifuge with water and acetone at 10,000 rpm for 10 min to remove the supernatant, and finally dry in a vacuum oven at 80° C. for 10 h.
[0021] In this embodiment, the carbon quantum dot material rich in various types of zinc-philic functional groups synthesized by the hydrothermal strategy can improve the electric field distribution on the zinc metal surface, thereby uniformly depositing zinc ions and nucleating the process.
[0022] Carbon quantum dot materials were synthesized by dehydration condensation of terephthalaldehyde and trifluoromethylbenzonitrile-acetonitrile.
[0023] The second embodiment of the present invention provides a carbon quantum dot material. It can provide a large number of zinc-philic sites and improve the surface electric field, promote the transmission process of zinc ions, and make it have excellent cycle stability. The third embodiment of the present invention provides a method for preparing a modified zinc foil, which specifically comprises the following steps: Step S2, mixing polyacrylonitrile (PAN) powder and DMF at a mass ratio of 0.5-1:9 to obtain a PAN spinning solution; Step S3, dispersing the carbon quantum dot material in the PAN spinning solution at a mass ratio of the carbon quantum dot material to the PAN powder of 0.5-1:10, and magnetically stirring for 6 hours to obtain a PCDs mixed solution, i.e., a mixed spinning liquid; wherein the carbon quantum dot material is the above-mentioned carbon quantum dot material; Step S4, spinning the mixed spinning liquid onto the surface of the zinc foil by electrospinning. Specifically, pour the mixed spinning liquid into a syringe, and wrap the zinc foil on the surface of a receiving device (drum), and perform directional spinning at 45-60 degrees to the receiving device. The electrospinning speed is 0.5-2 mL h -1 After the electrospinning is completed, the drying time is 4-8 h to obtain Zn@PCDs, i.e., modified zinc foil.
[0024] In this embodiment, the PCDs fiber layer obtained by combining the carbon quantum dot material and PAN powder through electrospinning technology, due to the potential difference, the spinning solution is randomly and evenly sprayed on the surface of the zinc foil by the needle to form a large number of porous structures. The high molecular weight of the PAN material ensures the high elasticity and high toughness of the fiber, thereby forming a protective layer with excellent mechanical properties, which can effectively inhibit volume expansion during high current or high capacity cycles. The internally doped carbon quantum dot material contains a large number of polar functional groups, thus improving the ionic conductivity of the material to a certain extent. The large amount of F elements inside can enhance the bonding force between the protective layer and the zinc metal and reduce the surface energy of the zinc (002) crystal plane, so that the zinc ions preferentially deposit on the (002) crystal plane.
[0025] The fourth embodiment of the present invention provides a modified zinc foil, which is obtained by using the above-mentioned preparation method of the modified zinc foil.
[0026] The fifth embodiment of the present invention provides an application of a modified zinc foil in a negative electrode material of a zinc ion battery.
[0027] The modified zinc foil is used as the negative electrode material of aqueous zinc ion battery. The carbon quantum dot material with rich negatively charged functional groups can repel sulfate ions in the electrolyte, thereby inhibiting the formation of by-products. The F element reduces the binding energy of zinc (002) crystal surface to a certain extent, and preferentially deposits zinc ions on the (002) crystal surface. In addition, the zinc-philic hydrophobic protective layer can reduce [Zn(H2O)6] 2+ The desolvation energy barrier facilitates the rapid desolvation and nucleation process, while inhibiting the occurrence of side reactions. Therefore, the protective layer deposited on the surface of the zinc negative electrode by the preparation method of the present invention can ensure uniform and stable deposition of the zinc metal negative electrode under different current densities.
[0028] Example 1 Step S10, dissolve 13 g of p-trifluoromethylbenzonitrile in 50 mL of 1 mol L -110g of terephthalaldehyde was added to the mixture and ultrasonically treated for 10min. The solvent was then transferred to an autoclave and subjected to a hydrothermal reaction at 160°C for 2h. After cooling to room temperature, the mixture was diluted with 100mL of deionized water and centrifuged at 10000rpm for 10min with water and acetone to remove the supernatant. Finally, the FN-CDs material, i.e., carbon quantum dot material, was obtained after drying at 80°C in a vacuum oven for 10h.
[0029] The FN-CDs material obtained in this example was tested, and the test results are shown in Figure 1-2 , Figure 1 The spots in the image are carbon quantum dots. Figure 1 It can be seen that the size distribution of carbon quantum dots is uniform, and the diameter is about 3 nm. Figure 2 Fourier transform infrared (FT-IR) analysis of the surface functional groups of CDs ( Figure 2 ). Obviously, 1687 and 2220 cm –1 The peaks near are associated with the stretching of -CHO and -CN groups. The vibration at 1300 cm –1 The peak is reached near , which can be attributed to CF stretching, further indicating the successful preparation of FN-CDs, whose abundant internal functional groups are expected to increase more zinc-philic deposition sites and improve zinc anode deposition.
[0030] Step S20, mixing PAN powder and DMF at a mass ratio of 1:9 to obtain a PAN spinning solution; Step S30, transferring the FN-CDs into the PAN spinning solution and magnetically stirring for 6 h to obtain a PCDs mixed solution; Step S40, pour the PCDs mixed solution into the syringe, wrap the zinc foil on the surface of the drum, and perform directional spinning at 45° to the drum at a spinning rate of 1 mL h -1 , Zn@PCDs, i.e. modified zinc foil, is obtained. The synthesis diagram is shown in Figure 3 shown.
[0031] The Zn@PCDs modified negative electrode obtained in this embodiment was tested, and the test results are shown in Figure 4 ,from Figure 4 From the SEM images at different magnifications, it can be seen that the PCDs fibers are distributed very evenly and densely, with a diameter of about 300 nm; the internal fibers show a 3D network interconnected structure. Figure 4 The TEM image of a shows that there are large dark areas in the PAN fibers according to high-resolution TEM analysis. The elemental composition and distribution of the samples were analyzed by energy dispersive X-ray spectroscopy (EDX), and the uniformity of the distribution of FN-CDs nanoparticles was determined. Figure 4 The EDX image results in b show that the distribution of C, N, O and F is relatively uniform, thus proving the uniform distribution of FN-CDs and the successful preparation of the PCDs layer.
[0032] The Zn@PCDs obtained in this example were tested, and the test results are shown in Figure 5 ,from Figure 5 It can be seen that the thickness of the PCDs protective layer is about 20 μm.
[0033] Step S50, Zn@PCDs is used as the negative electrode of the zinc ion battery, and the action mechanism diagram is as follows Figure 6 As shown in the figure, the surface of pure zinc produces a large number of dendrites and a series of side reactions due to the uneven electric field distribution during the cycle. Such as hydrogen evolution, corrosion, passivation, etc. The modified negative electrode surface effectively inhibits the growth of dendrites and the generation of side reactions due to the presence of a protective layer. Therefore, a zinc ion symmetric battery was assembled using the same material as the counter electrode; a zinc ion half-battery was assembled using copper foil as the counter electrode; and a zinc ion full battery was assembled using MnO2 as the counter electrode. The performance of the battery was tested and compared with the battery without a negative electrode protective layer. The results are shown in the figure. Figure 7-8 As shown, from Figure 7 It can be seen that under different current density conditions, the rate performance of Zn@PCDs in this embodiment is better. Figure 8 It can be seen that under the conditions of different current densities, the cycle performance of Zn@PCDs in this embodiment is better.
[0034] Example 2 Step S10, dissolve 10 g of p-trifluoromethylbenzonitrile in 50 mL of 1 mol L -1 100 mL of deionized water, and then centrifuged at 10,000 rpm with water and acetone for 10 minutes to remove the supernatant. Finally, the FN-CDs material was obtained after drying at 80 °C for 10 hours in a vacuum oven.
[0035] The FN-CDs material and PVDF powder obtained in this example were added into a beaker containing 2 mL of DMF solution at a mass ratio of 8:2, and magnetically stirred for 6 h to obtain a FN-CDs mixed slurry; The FN-CDs mixed slurry obtained in this example was evenly coated on the zinc metal surface with a 5μm scraper for testing and characterization. The protective layer thickness was about 2μm, the surface was flat and smooth, and the distribution of C, N, O and F inside was relatively uniform, thus proving the successful preparation of the FN-CDs protective layer.
[0036] The Zn@FN-CDs obtained in this example were subjected to electrochemical tests. The Zn@FN-CDs were used as the negative electrode of the zinc ion battery, and the same material was used as the counter electrode to assemble the zinc ion symmetric battery; copper foil was used as the counter electrode to assemble the zinc ion half-cell; MnO2 was used as the counter electrode to assemble the zinc ion full battery and test the battery performance, and compared with the battery without the negative electrode protective layer. Under different current density conditions, the rate performance and cycle performance of the Zn@FN-CDs in this example are better.
[0037] Example 3 The carbon quantum dot material was prepared by the scheme of Example 1, except that: In step S10, 5 g of trifluoromethylbenzonitrile is dissolved in 50 mL of 1 mol L -1 The mixture was then added to a sodium hydroxide solution and ultrasonically treated for 10 min until the material was uniformly dispersed. Subsequently, 2 g of terephthalaldehyde was added to the mixture, and the solvent was then transferred to an autoclave. After hydrothermal reaction at 180 °C for 2 h, the mixture was naturally cooled to room temperature, diluted with 100 mL of deionized water, and then centrifuged with water and acetone at 10,000 rpm for 10 min to remove the supernatant. Finally, the carbon quantum dot material was obtained after drying at 80 °C for 10 h in a vacuum oven.
[0038] The carbon quantum dot material obtained in this example is light yellow and contains a large number of cyano groups and aldehyde groups, which can further regulate the orderly and uniform deposition of zinc ions on the surface of zinc metal.
[0039] Example 4 The carbon quantum dot protective layer material was prepared by the scheme of Example 1, except that: In step S20, PAN powder and DMSO are mixed at a mass ratio of 1:9 to obtain a PAN spinning solution. The carbon quantum dot spinning solution obtained in this embodiment is more evenly dispersed, has stronger adhesion on the zinc metal surface, and is more stable during the battery cycle.
[0040] Example 5 The carbon quantum dot material was prepared by the scheme of Example 2, except that: In step S10, the mass ratio of trifluoromethylbenzonitrile to terephthalaldehyde is 3:1, and the obtained carbon quantum dot material has a higher proportion of cyano groups and F elements inside, which has a better effect on inducing 002 crystal surface modification for zinc metal negative electrode.
[0041] The above are only preferred embodiments of the present application, and are not intended to limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. A method for preparing a carbon quantum dot material, characterized in that: include: The terephthalaldehyde and trifluoromethylbenzonitrile acetonitrile are placed in a sodium methoxide solution for hydrothermal reaction to obtain a carbon quantum dot material.
2. The method for preparing the carbon quantum dot material according to claim 1, characterized in that: The mass ratio of the terephthalaldehyde to the trifluoromethylbenzonitrile is 1:1-2.
3. The method for preparing the carbon quantum dot material according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 120-180° C. and the time is 1-5 hours.
4. The method for preparing the carbon quantum dot material according to claim 1, characterized in that: The sodium methoxide concentration is 0.5-1.5 mol L -1 .
5. A carbon quantum dot material, characterized in that: The carbon quantum dot material is obtained by the preparation method of any one of claims 1 to 4, wherein the carbon quantum dot material has zinc-philic nucleation sites.
6. A method for preparing a modified zinc foil, characterized in that: include: Mixing PAN powder with DMF to obtain PAN spinning solution; Dispersing the carbon quantum dot material in the PAN spinning solution to obtain a mixed spinning liquid; wherein the carbon quantum dot material is the carbon quantum dot material according to claim 5; The mixed spinning liquid is spun onto the surface of the zinc foil by electrostatic spinning to obtain a modified zinc foil.
7. The method for preparing the modified zinc foil according to claim 6, characterized in that: The mass ratio of the PAN powder to the DMF is 0.5-1:9, and the ratio of the carbon quantum dot material to the PAN spinning solution is 0.5-1:
10.
8. The method for preparing the modified zinc foil according to claim 7, characterized in that: The electrospinning process specifically includes: pouring the mixed spinning liquid into a syringe, wrapping the zinc foil on the surface of the receiving device, and performing directional spinning at 45-60 degrees to the receiving device; the electrospinning speed is 0.5-2 mL h -1 , the drying time is 4-8 h.
9. A modified zinc foil, characterized in that: The modified zinc foil is obtained by the preparation method of any one of claims 6 to 8.
10. Use of the modified zinc foil as claimed in claim 9 in a negative electrode material of a zinc ion battery.
Citation Information
Patent Citations
Preparation method of PVDF-CTFE-based lithium-sulfur battery composite diaphragm
CN114204208A
MOF-808 / PAN-coated Zn metal negative electrode and preparation method and application thereof
CN117038836A
High-entropy carbon quantum dot nano material as well as preparation method and application thereof
CN117143598A
Polyanionic positive electrode composite material as well as preparation method and application thereof
CN117766743A
Fluorine-doped carbon quantum dot catalyst for efficiently electro-catalyzing carbon dioxide to reduce methane as well as preparation method and application of fluorine-doped carbon quantum dot catalyst
CN117867555A
Cited By
Coaxial composite fiber and preparation method and application thereof
CN120591917A